Synthesis of Sulfated Carbohydrates Using Sulfuryl Imidazolium Salts - Desoky, Ahmed (University of Waterloo, 2010)
Sulfated polysaccharides are widespread in nature. These compounds are implicated in a wide variety of important biological processes such as blood clotting, cell adhesion, and cell–cell communication. However, detailed characterization of their specific biological roles has proved to be very challenging. One reason for this is that the synthesis of even relatively small sulfated oligosaccharides still remains a considerable challenge. A general approach to the synthesis of sulfated carbohydrates was examined in which the sulfate group is incorporated at the beginning of the syntheses as a protected sulfodiester. Towards this end, a series of modified sulfuryl imidazolium salts were prepared and examined as reagents for incorporating 2,2,2-trichloroethyl-protected sulfate esters into monosaccharides.. A more efficient sulfating agent was obtained by incorporating a methyl group at the 2-position of the imidazolium ring. O-Sulfations that required prolonged reaction times and a large excess of the original sulfuryl imidazolium salt (SIS) which bears no alkyl groups on the imidazolium ring, were more readily achieved using the new reagent. Direct regioselective incorporation of TCE-protected sulfates into monosaccharides was achieved using the new imidazolium salt. We have also shown that the new SIS can also be used for the direct disulfation of monosaccharides and that trisulfated monosaccharides can also be prepared from the disulfated compounds. SIS’s bearing the TFE and phenyl groups, were readily prepared. In most instances, both TFE- and phenyl protected sulfated carbohydrates were easily prepared in good yields using SIS’s. Deprotection of the TFE group from secondary sulfates in carbohydrates and aryl sulfates was achieved in excellent yields using NaN3 in DMF. We applied the sulfate protecting group strategy towards the total synthesis of the tetrasaccharide portion of a disulfated glycosphingolipid called SB1a. Efficient routes were developed for the construction of the left- and right-hand protected disaccharide portions of the SB1a tetrasaccharide.
Keywords: sulfated carbohydrates; Imidazolium Salts; Chemistry